A new species of Rhododendron (Ericaceae) from northeastern Yunnan, China - Tian, Xiao-Ling; Chang, Yu-Hang; Neilsen, Jens; Wang, Si-Hai; Ma, Yong-Peng (Phytotaxa, 2019)
The genus Rhododendron Linnaeus (1753: 392) has more than 1,000 species that have been recognized in the temperate areas of the world (Chamberlain et al. 1996). In China, ca. 600 species of Rhododendron have been confirmed, including numerous species described after the publishing of Flora of China (Chen et al. 2010, Chen et al. 2012, Ma et al. 2013, Liao et al. 2015, Ma et al. 2015, Cai et al. 2016). They occur in most of China’s provinces except Xinjiang and Ningxia (Ma et al. 2014). Among these provinces, Yunnan, Sichuan and Tibet have the greatest diversity.